Arctic dipole anomaly and its contribution to sea ice export from the Arctic Ocean in the 20th century - Watanabe, Eiji; Wang, Jia; Sumi, Akimasa; Hasumi, Hiroyasu (Geophysical research letters, 2006)
The winter dipole anomaly (DA) in the Arctic atmosphere and its contribution to sea ice export are investigated by using a high‐resolution coupled global general circulation model. The spatial distributions of the first two leading EOF modes of winter mean sea level pressure (SLP) and geopotential height at 500 hPa north of 70°N obtained by the long‐term simulation (1900–2010) are highly similar to those derived from the National Center for Environmental Prediction and the National Center for the Atmospheric Research (NCEP/NCAR) reanalysis datasets (1948–2004). The first‐leading mode corresponds to the Arctic Oscillation (AO). The DA is defined as the second‐leading mode. The AO and DA account for 59% and 19% of the total variance, respectively. Composite spatial patterns of SLP, sea ice thickness and velocity in the extreme years when both the absolute values of principal component (PC1 and PC2) exceed 1.0 standard deviation indicate that the DA plays a great important role in sea ice export from the Arctic Ocean to the Greenland Sea due to its strong meridionality. Sea ice export is highly promoted (restricted) in the positive (negative) DA phase. The dependence of sea ice export on the DA is comparable to or rather larger than that on the AO.